Fun with English Activity for Junior High School 8 Palopo - Ermawati; Suherman, La Ode Achmad (Room of Civil Society Development, 2023)
This research is to enhance students’ communicative and English skills of students of Junior High School 8 Palopo, Indonesia. The method used is teaching and learning English with providing pre-test, applying fun with English activities, and giving post-test as the report. The procedures of applying the fun with English activity are giving ice breakers, applying games, explaining materials, grouping the students, providing practice, and evaluating the students’ achievement and the process of the activity. There are several games used in the activity, such as whispering, introducing other and total physical response. It shows that students are eager and interested in learning English that can be seen in their full participation in the Fun with English activity. Also, students are eager to communicate with others by providing communicative and fun activities that is emphasized in the grouping activities. This part enables students to communicate with their peers and tutors effectively. The implication of the study can be a reference for other school to apply the same activity and to collaborate with English Education Study Program to apply the similar activity to increase students’ communicative and English skills.